Recent advances in high-temperature PEM fuel cells - Pasupathi, Sivakumar; Calderon Gomez, Juan Carlos; Su, Huaneng; Reddy, Harikishan; Bujlo, Piotr; Sita, Cordellia; Pollet, Bruno G. (Hydrogen energy and fuel cells primers., 2016)
Hydrogen and Fuel Cells Primers is a series focused on Energy applications. Its concise volumes present those coming into this broad and multidisciplinary field with the most recent advances in each of its particular topics. They bring together information that has thus far been scattered in many different sources under one single title, which makes them a useful reference for industry professionals, researchers and graduate students, especially those starting in a new topic of research. This volume, Recent Advances in High Temperature PEM Fuel Cells, provides an up-to-date progress of High Temperature Polymer Electrolyte Membrane Fuel Cells (HTPEMFCs), including three critical subjects for this type of fuel cells: Membrane Electrode Assembly (MEA) development, stack development and systems development. The MEA and stack development sections cover the recent advances in this area and highlight the areas in most need of improvement. The systems development section focuses on stationary systems, mainly Combined Heat and Power (CHP), based on HTPEMFCs. Finally the conclusions summarize the recent advances of HTPEMFCs in all these areas and provide some insights for future developments. Prof. Bruno G. Pollet, Series Editor.